GAMBARAN TINGKAT PENGETAHUAN REMAJA TENTANG UPAYA PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) MELALUI STRATEGI 3M PLUS - Ni Wayan Eka Apriani; Ni Luh Gede Intan Saraswati; Theresia Anita Pramestit (Rena Cipta Mandiri, 2026)
Dengue hemorrhagic fever (DHF) is a public health problem that continues to occur and is a health challenge, especially in tropical climates, but it can basically be prevented through the implementation of the 3M Plus strategy. One of the prevention efforts that can be done is to increase knowledge, especially in adolescents, because knowledge plays an important role in shaping disease prevention behaviors. The purpose of this study is to find out the overview of adolescents' level of knowledge about Dengue Hemorrhagic Fever (DHF) prevention efforts through the 3M Plus strategy. This research is a descriptive research, using univariate analysis. The sample in this study amounted to 305 respondents, which were taken using the Probability Sampling technique in the Proportionate Stratified Random Sampling method. Based on the results of the study, the most respondents were found at the age of 14 years, namely 104 respondents (34.1%), male 166 respondents (54.4%). The level of adolescents' knowledge about dengue prevention efforts through the 3M Plus strategy showed that most of the respondents were in the category of sufficient knowledge, namely 148 respondents (48.5%). The results of the study show that the level of knowledge of adolescents in the category is enough to indicate that adolescents have received information about dengue prevention, but this understanding is not fully in-depth and uneven. This condition shows the need to strengthen health education in a sustainable manner so that adolescents' knowledge can increase and be applied in daily dengue prevention behavior.